The Existence of Spathodea Park in South Jakarta as a Medium for Education and Climate Change Mitigation - Edward Alfin; Tatan Zenal Mutakin (Proceeding International Conference on Digital Education and Social Science, 2024)
The existence of Spathodea Park is an open green space that contains various types of plants. This park is located in the Jagakarsa District of South Jakarta City. The purpose of this research is to understand the diversity of plants as a medium for knowledge and education, as well as their role in combating climate change. The research method is descriptive qualitative. Data collection used a purposive sampling approach. The results obtained show the diversity of plants in Spathodea Park, which includes 54 plant species. The presence of these 54 plant species plays a role in the carbon cycle, thus contributing to climate change mitigation. Spathodea South Jakarta as a Medium for Education and Climate Change Mitigation